Fragmentation of the oral judgment and the affectation of the quality of the judgment in the Superior Court of Justice of Tacna-2016. - Franco Apaza, Pedro David (2019)
The present research work deals with the fragmentation of the oral trial and the effect of the quality of the trial in the Criminal Court of the Superior Court of Justice of Tacna-2016, which was carried out with the purpose of determining if the fragmentation of the oral trial affects the quality of the trial in the Criminal Court of the Superior Court of Justice of Tacna-2016. For this, the following hypothesis was established. Probably the fragmentation of the hearing of the oral trial, considerably affect the quality of the trial in the Criminal Court of the Superior Court of Justice of Tacna-2016. The work corresponds to a basic type of investigation, an explanatory level; and, non-experimental design. For this purpose, the information obtained through the questionnaire applied to 170 legal professionals in criminal matters, the interview card for trial judges (04) and the analysis card (83 judgments) were considered; as instruments for measuring the variables: independent (fragmentation of oral judgment) and dependent variable (quality of judgment). The data obtained were tabulated and analyzed by tables and figures. Once the phase of analysis and interpretation of the results was completed, it was specified that: Probably the fragmentation of the hearing of the Oral Trial, considerably affects the quality of the trial in the Criminal Court of the Superior Court of Justice of Tacna-2016.